1971
DOI: 10.1037/h0030391
|View full text |Cite
|
Sign up to set email alerts
|

Authoritarianism and attitudes toward the Vietnam war as reflected in behavioral and self-report measures.

Abstract: This study tested the hypothesis that authoritarianism as measured by the California F Scale would be related to both behavioral and self-report measures of subjects' attitudes toward United States involvement in the Vietnam war. In a test of the hypothesis, the F scale and a self-report questionnaire pertaining to the Vietnam war were administered to 131 introductory psychology students. Sixty-five of these students actively demonstrated against United States involvement in the Vietnam war by not attending cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
2

Year Published

1972
1972
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 5 publications
0
22
0
2
Order By: Relevance
“…Similarly, authoritarians tested during the loyalty-oath controversy at the University of California were shown to favor such oaths for faculty members (Handlon & Squier, 1955). Support for constituted authority also was shown in attitudes toward the Vietnam war (Izzett, 1971;Granberg & Corrigan, 1971). Opposition to socialized medicine is another of the many consistent correlates of authoritarian ideology as measured by the F-Scale (Mahler, 1953).…”
Section: Authoritarianism and Political Ideologymentioning
confidence: 89%
“…Similarly, authoritarians tested during the loyalty-oath controversy at the University of California were shown to favor such oaths for faculty members (Handlon & Squier, 1955). Support for constituted authority also was shown in attitudes toward the Vietnam war (Izzett, 1971;Granberg & Corrigan, 1971). Opposition to socialized medicine is another of the many consistent correlates of authoritarian ideology as measured by the F-Scale (Mahler, 1953).…”
Section: Authoritarianism and Political Ideologymentioning
confidence: 89%
“…For instance, SDO is related to support for U.S. action in the 1991 Gulf War (Pratto et al, 1994;Sidanius & Liu, 1992), and the recent U.S.-led war against Iraq (McFarland, 2005). Moreover, authoritarianism correlated with support for U.S. action in the Vietnam War (Izzett, 1971), the 1991 Persian Gulf War (Doty, Winter, Peterson, & Kemmelmeier, 1997;Duncan & Stewart, 1995), and the recent U.S.-led war against Iraq (McFarland, 2005). This evidence could be interpreted as supporting a generalized influence of SDO and RWA on support for wars targeting lower status groups.…”
Section: Studymentioning
confidence: 99%
“…Green et al [2003], for example, found that perceptions of the causes of loneliness were not related to levels of extraversion. Previous research has suggested that understanding about the causes and justice of a war maybe affected by holding authoritarian beliefs [Doty et al, 1997;Izzet, 1971]; hence, we might expect differences between high and low authoritarians in their representations of September 11th. Reser and Muncer [2004] found, however, that there were no simple effects of either right-wing authoritarian attitude or just world beliefs.…”
Section: Introductionmentioning
confidence: 96%